A feasibility study on organic lotus pollen tea as consumer product - Duangtip Hongsamoot; Suvarin Bumroongsook (My University, 2015)
Lotus pollen tea, in particular, contains potent antioxidants.The first step of this study was the screening for 3 desired qualities of 4 varieties of lotus (NelumbonuciferaGaertn): Sattabongkutt, Buntharik, Sattabutt, and Patum. The 3 desired qualities were as follows: high pollen yield; potent antioxidant activity; and favorable aroma, flavor, and color to a panel of testers. The results of the screening were the following: one, the pollen productions of a flower of each of the 4 varieties stated above were 1.28, 3.11, 0.43, and 1.83 gm, respectively; two, Buntharik had the highest antioxidant capacity at a trolox equivalent of 499.48 µg/ml or 59.94 mg/serving and at a total polyphenol equivalent of gallic acid of 63.26 µg/ml or 7.59 mg/serving; and three, the highest-rated variety in a hedonic test of overall preference was Buntharik. Thus, the Buntharik tea was chosen for the consumer acceptance studies conducted with 90 tea testers with equal number of males and females. The finding was found that males preferred this tea over females; panelists over 30 years old gave the highest score on overall preference; their level of acceptance was fairly acceptable, at 50%, but their purchase intention was lower, at 27.78%.
Keywords: Trolox; Chromatography in Natural Products